The Influence of Corner Gussets over the Lightweight Tubular Latticed Beams. (2015) - Dima, Gabriel
Abstract: The aircraft lightweight welded structures employ circular section members using Pratt or Warren configuration. If in civil engineering gussets are mainly used for bracing connection or as shoulder bracket for beams and columns, in aerospace they are used for a better stress distribution in joints. This solution may be used for design or for structural weight saving programs. The article analyses the possibility to use gussets in order to obtain lighter beams. After designing of similar beams according existing recommendations, their static and buckling behavior was investigated taking into consideration the stress values, rigidity and mass. The assessment was done after the criteria of the same mass for compared beams. The results are discussed from the lightweight, rigidity and fatigue point of view. Conclusions and recommendation for practical design are given.